Down‐regulated expression of microRNA‐338‐5p contributes to neuropathology in Alzheimer's disease. Issue 3 (21st December 2018) - Qian, Qi; Zhang, Jian; He, Fang-Ping; Bao, Wang-Xiao; Zheng, Ting-Ting; Zhou, Dong-Ming; Pan, Hong-Yu; Zhang, Heng; Zhang, Xiao-Qin; He, Xiao; Sun, Bing-Gui; Luo, Ben-Yan; et al.
ABSTRACT: Alzheimer's disease (AD) is a leading cause of dementia. However, the mechanisms responsible for development of AD, especially for the sporadic variant, are still not clear. In our previous study, we discovered that a small noncoding RNA (miR‐188‐3p) targeting β‐site amyloid precursor protein cleaving enzyme (BACE)‐l, a key enzyme responsible for Aβ formation, plays an important role in the development of neuropathology in AD. In the present study, we identified that miR‐338‐5p, a new miRNA that also targets BACE1, contributes to AD neuropathology. We observed that expression of miR‐338‐5p was significantly down‐regulated in the hippocampus of patients with AD and 5XFAD transgenic (TG) mice, an animal model of AD. Overexpression of miR‐338‐5p in the hippocampus of TG mice reduced BACE1 expression, Aβ formation, and neuroinflammation. Overexpression of miR‐338‐5p functionally prevented impairments in long‐term synaptic plasticity, learning ability, and memory retention in TG mice. In addition, we provide evidence that down‐regulated expression of miR‐338‐5p in AD is regulated through the NF‐κB signaling pathway. Our results suggest that down‐regulated expression of miR‐338‐5p plays an important role in the development of AD.—Qian, Q., Zhang, J., He, F.‐P., Bao, W.‐X., Zheng, T.‐T., Zhou, D.‐M., Pan, H.‐Y., Zhang, H., Zhang, X.‐Q., He, X., Sun, B.‐G., Luo, B.‐Y., Chen, C., Peng, G.‐P. Down‐regulated expression of microRNA‐338‐5p contributes to neuropathology in Alzheimer's disease. FASEB J. 33, 4404–4417 (2019). www.fasebj.org